Conformity of Legislation Formation Theory with Modern Legislation Practice: Implementing Public Aspirations - Utami, Tanti Kirana; Rahayu, Anisa Fuji; Chatlina, Chiara Belva; Putri Mulya, Tasya Azmawanti (Indonesian Journal of Law and Justice, 2025)
This research aims to analyse the compatibility between the theory of legislation formation and the practice of legislation in the modern era, especially in relation to the implementation of public aspirations. In the context of a democratic legal state like Indonesia, public participation in the legislative process is not only a constitutional right, but an essential element to ensure the legitimacy and quality of legal products. This research uses a normative juridical approach combined with an empirical juridical approach. Data was obtained through a literature study of legislation and legal literature which was analysed qualitatively. The results show that public participation in the legislative process, as guaranteed in Article 96 of Law No. 12/2011, still faces various challenges, such as the lack of transparency and the dominance of political interests. Modern legislative practices such as the Omnibus Law show the potential for efficiency, but risk creating social justice imbalances if not accompanied by meaningful community involvement. The principles of social justice mandated by Pancasila and the 1945 Constitution must be the foundation in every stage of legislation to ensure inclusive and responsive laws. In conclusion, harmonisation between the theory and practice of law formation is needed so that the law is not only a tool of control, but also a means of empowerment and protection of community rights. Regulatory reform requires broad social dialogue, in-depth legal studies, and open public control mechanisms to strengthen substantive democracy.